Shaken, Not Stunted? Global Evidence on Natural Disasters, Child Growth and Recovery - John Cruzatti C.; Matthias Rieger (Institute of Labor Economics (IZA), 2024)
A substantial share of the world's children reside in disaster-prone areas and suffer from stunted growth. Child growth in the first 1000 days of life can falter depending on health endowments and investments. We investigate growth faltering and catch-up in children exposed to comparable earthquakes in utero. Our analysis leverages within cluster or mother variation, controls for temporal trends, and utilizes a global sample of localized data spanning several decades. On average, we document modest adverse effects on children's height that are more pronounced when earthquakes are more unexpected and higher in magnitude. These average effects, however, conceal negative short-term effects and posterior recovery mechanisms via parental health investments, economic recouping, and foreign aid, which facilitate subsequent catch-up growth of children. We discuss our findings and contributions within the literature on child health and disasters, which has largely been confined to single-country studies.
Keywords: I15; I18; J13; O15; Q54; 330; child health; natural disasters; global evidence; local data; aid